Developing Performance Metrics for Science and Technology Programs: The Case of the Manufacturing Extension Partnership Program. - Voytek, Kenneth P.; Lellock, Karen L.; Schmit, Mark A. (Economic Development Quarterly, 2004)
Part of a special issue on science- and technology-based economic development. The writers explore the development, implications, and limitations of a series of performance measures to discover the success of individual Manufacturing Extension Partnership (MEP) centers. They note that the measures mark a transformation in how MEP judges and evaluates center performance and a challenge in terms of how they are employed, how they are interpreted, and how they are limited.